Implementasi Model Pembelajaran Klasik dan Model Pembelajaran Kelompok PAUD Bintang Ananda Botoran Tulungagung - Choiroyaroh, Siti Istatik (Absorbent Mind, 2024)
Early childhood education should have optimal, effective, efficient, productive, and accountable policies and coordinate well with government, family, and community support to produce positive and maximum impacts. This study aims to explain the conditions of learning management at PAUD Bintang Ananda, which experiences differences in learning models applied in institutions; institutions apply two learning models, namely classical and group. This research method uses a qualitative descriptive approach, which examines research objects naturally according to facts and data in the field. Data collection techniques through interviews, observations, and documentation studies with research time during April 2024. Based on the results of the study show that there are differences in learning models applied in institutions; these differences are due to several factors, such as lack of teaching staff, student understanding, and lack of facilities that support the learning process; these results make institutions have to make decisions about the implementation of the right learning model according to the interests and abilities of children. So, the institution has arranged and prepared everything to implement the learning model that will be applied, focusing on learning models that can develop children's abilities and pay attention to children's interests.